Meta-analytic evidence on the efficacy of hypnosis for mental and somatic health issues: a 20-year perspective - Rosendahl, Jenny; Alldredge, Cameron T.; Haddenhorst, Antonia (Frontiers in Psychology, 2024)
Introduction: Documented use and investigation of hypnosis spans centuries and its therapeutic use has received endorsement by multiple medical association. We conducted a comprehensive overview of meta-analyses on the efficacy of hypnosis to provide a foundational understanding of hypnosis in evidence-based healthcare, insight into the safety of hypnosis interventions, and identification of gaps in the current research literature.Methods: In our systematic review, meta-analyses of randomized controlled trials on the efficacy of hypnosis in patients with mental or somatic health problems compared to any control condition published after the year 2000 were included. A comprehensive literature search using Medline, Scopus, PsycINFO, The Cochrane Library, HTA Database, Web of Science and a manual search was conducted to identify eligible reviews. Methodological quality of the included meta-analyses was rated using the AMSTAR 2 tool. Effect estimates on various outcomes including at least three comparisons (k ≥ 3) were extracted in transformed into a common effect size metric (Cohen´s d). If available, information on the certainty of evidence for these outcomes (GRADE assessment) was obtained.Results: We included 49 meta-analyses including 261 distinct primary studies. Most robust evidence was reported for hypnosis in patients undergoing medical procedures (12 reviews including 79 distinct primary studies) and in patients with pain (4 reviews, 65 primary studies). There was a considerable overlap of the primary studies across the meta-analyses. Only nine meta-analyses had a high methodological quality. Reported effect sizes comparing hypnosis against control conditions ranged from d = -0.04 to d = 2.72. Of the reported effects, 25.4% were medium (d ≥ 0.5), and 28.8% were large (d ≥ 0.8).Discussion: Our findings underline the potential of hypnosis to positively impact various mental and somatic treatment outcomes, with the largest effects in populations of children/adolescents and in patients undergoing medical procedures. Future research should focus on the investigation of